Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes